Durability as an independent parameter of endurance performance in cycling - Barsumyan, A.; Soost, C.; Shyla, R.; Graw, J. A.; Bliemel, C.; Burchard, R. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Recent advances in sport physiology have shown, that higher fatigue resistance predicts outstanding performance in endurance sport. However, so far there is no clear consensus on how to test durability in the field or in a laboratory. Protocols of the few existing studies are only suitable for professional male cyclists while most coaches work primarily with amateur athletes. Moreover, it is currently unclear whether durability is dependent on traditional parameters of endurance performance, such as functional threshold power (FTP) or maximal oxygen uptake (VO2 max).